Adomian decomposition method applied to Klien Gordon and nonlinear wave equation. Issue 5 (4th July 2021) - Alkarawi, Ali H.; Al-Saiq, Inaam. R.
Abstract: In this research we focus on studying the Adomian Decomposition method (ADM) based on the operators. However, we are using Adomian Decomposition method to solve linear and non-linear partial differential equations such as (the linear wave equation, nonlinear Klein Gordon equation, the non-linear wave equation, the diffusion equation and some non-linear partial differential equations). When we compared the results with the actual solution if it exist or numerical solution if it does not exist, we obtained the accurate and effective method